2022
DOI: 10.1021/acsaelm.2c00767
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and Magnetic Properties of Hexagonal ErFeO3 Epitaxial Films

Abstract: Hexagonal rare-earth iron oxides (h-RFeO3) exhibit both magnetic and ferroelectric orders. The ferroic properties depend on the R ionic radius; for example, they are antiferroelectric (AFE) when R = Dy and ferroelectric (FE) when R = Tm, Yb, and Lu. However, insights into the ferroelectric properties of h-ErFeO3, characterized by an intermediate ionic radius, are hampered by its severe electric leakage current. In this study, we successfully prepared h-ErFeO3 films with limited electric leakage current via ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The calculated lattice parameters ( a , c, and volume) were (6.11 Å, 11.9 Å, 193 Å 3 ), (6.07 Å, 11.9 Å, 190 Å 3 ), and (6.00 Å, 11.9 Å, 186 Å 3 ) for the h -DyFeO 3 , h -ErFeO 3 , and h -LuFeO 3 films, respectively. By contrast, it was reported that the lattice parameters of the epitaxial films of h -DyFeO 3 , h -ErFeO 3 , and h -LuFeO 3 were (6.24 Å, 11.82 Å, 199 Å 3 ), (6.03 Å, 11.86 Å, 187 Å 3 ), and (5.92 Å, 11.77 Å, 179 Å 3 ), respectively. ,, The tendency that the a -axis length and volume decreased with a decreasing R ion size was consistent. However, the decrease in the films on glass was smaller than that in epitaxial films, likely due to the difference in the force applied to the films by the substrates between the epitaxial and polycrystalline growths.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The calculated lattice parameters ( a , c, and volume) were (6.11 Å, 11.9 Å, 193 Å 3 ), (6.07 Å, 11.9 Å, 190 Å 3 ), and (6.00 Å, 11.9 Å, 186 Å 3 ) for the h -DyFeO 3 , h -ErFeO 3 , and h -LuFeO 3 films, respectively. By contrast, it was reported that the lattice parameters of the epitaxial films of h -DyFeO 3 , h -ErFeO 3 , and h -LuFeO 3 were (6.24 Å, 11.82 Å, 199 Å 3 ), (6.03 Å, 11.86 Å, 187 Å 3 ), and (5.92 Å, 11.77 Å, 179 Å 3 ), respectively. ,, The tendency that the a -axis length and volume decreased with a decreasing R ion size was consistent. However, the decrease in the films on glass was smaller than that in epitaxial films, likely due to the difference in the force applied to the films by the substrates between the epitaxial and polycrystalline growths.…”
Section: Resultsmentioning
confidence: 87%
“…As shown in Figure (b), the ferromagnetic hysteresis of the film at 20–50 K was more clearly observed than that at 2–10 K. In h-R FeO 3 , there are four types of possible magnetic configurations (Γ 1 –Γ 4 ), and only the Γ 2 -type configuration allows the nonzero net magnetization along the c -axis direction owing to the Dzyaloshinskii–Moriya interaction . Therefore, the magnetic phase transition seems to reflect the reconfiguration of magnetic structures between Γ 2 and Γ x ( x = 1, 3, or 4). ,, …”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations